Malassezia-Associated Skin Diseases, the Use of Diagnostics and Treatment - Saunte, Ditte M. L.; Gaitanis, George; Hay, Roderick James (Frontiers in Cellular and Infection Microbiology, 2020)
Yeasts of the genus, Malassezia, formerly known as Pityrosporum, are lipophilic yeasts, which are a part of the normal skin flora (microbiome). Malassezia colonize the human skin after birth and must therefore, as commensals, be normally tolerated by the human immune system. The Malassezia yeasts also have a pathogenic potential where they can, under appropriate conditions, invade the stratum corneum and interact with the host immune system, both directly but also through chemical mediators. The species distribution on the skin and the pathogenetic potential of the yeast varies between different Malassezia related diseases such as head and neck dermatitis, seborrheic dermati-tis, pityriasis versicolor, and Malassezia folliculitis. The diagnostic methods used to confirm the presence of Malassezia yeasts include direct microcopy, culture based methods (often a combina-tion of morphological features of the isolate combined with biochemical test), molecular based methods such as Polymerase Chain Reaction techniques, and Matrix Assisted Laser Desorp-tion/Ionization – Time Of Flight mass spectrometry and the chemical imprint method Raman spec-troscopy. Skin diseases caused by Malassezia are usually treated with antifungal therapy and if there are associated inflammatory skin mechanisms this is often supplemented by anti-inflammatory therapy. The aim of this paper is to provide an overview of Malassezia related skin disease, diagnostic meth-ods and treatment options.